THE INFLUENCE OF ENTREPRENEURIAL MOTIVATION AND ENTREPRENEURIAL CHARACTERISTICS ON THE SUCCESS OF RONO DANGE MICRO-ENTERPRISE IN LERO VILLAGE, SINDUE DISTRICT, DONGGALA REGENCY - Imel Amanda; Lina Mahardiana; Andi Indriani Ibrahim; Moh Ali Murad (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of entrepreneurial motivation and entrepreneurial characteristics on the success of rono dange micro-enterprises in Lero Village, Sindue District, Donggala Regency. The study used a quantitative method with an associative approach. The study population consisted of 30 rono dange entrepreneurs and the entire population was sampled through a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS version 25. The results showed that entrepreneurial motivation had a positive and significant effect on business success with a calculated t value of 3.736 and a significance of 0.001. Entrepreneurial characteristics also had a positive and significant effect on business success with a calculated t value of 3.645 and a significance of 0.001. Simultaneously, entrepreneurial motivation and entrepreneurial characteristics had a positive and significant effect on business success with a calculated F value of 183.857 and a significance of 0.000. The coefficient of determination (R²) value of 0.932 indicates that 93.2% of the variation in business success can be explained by these two independent variables. and the remaining 6.8% is influenced by other variables outside this research model . The results of this study prove that increasing entrepreneurial motivation and entrepreneurial characteristics can increase the success of the rono dange micro-business in Lero Village.